2011
DOI: 10.1128/aac.00491-10
|View full text |Cite
|
Sign up to set email alerts
|

ISAba825, a Functional Insertion Sequence Modulating Genomic Plasticity and bla OXA-58 Expression in Acinetobacter baumannii

Abstract: ISAba825, an insertion sequence found inactivating Acinetobacter baumannii carO, was tagged with a kanamycin (Kn) resistance cassette. ISAba825::Kn effectively transposed in A. baumannii, showing preference for short, AT-enriched target sequences, generating 6-to 9-bp target duplications. Additionally, we detected the presence of ISAba825 upstream of a plasmid-borne bla OXA-58 gene, generating a hybrid promoter largely enhancing its expression and leading to carbapenem resistance. Overall, a role for ISAba825 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…Still, A. baumannii clinical strains bearing IS-mediated carO interruptions have so far been detected only among carbapenem-resistant isolates (21,26,29). Thus, the IS-mediated inactivation of carO, or the HGT-mediated exchange of particular carO variants, by reducing carbapenem influx through the OM may act synergistically with other mechanisms present in some genetic backgrounds (1,12,13,18,20,21,34,35,38,39,47,49,51), therefore resulting in an increased fitness phenotype under carbapenem pressure. The possible selected combinations are currently under study in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Still, A. baumannii clinical strains bearing IS-mediated carO interruptions have so far been detected only among carbapenem-resistant isolates (21,26,29). Thus, the IS-mediated inactivation of carO, or the HGT-mediated exchange of particular carO variants, by reducing carbapenem influx through the OM may act synergistically with other mechanisms present in some genetic backgrounds (1,12,13,18,20,21,34,35,38,39,47,49,51), therefore resulting in an increased fitness phenotype under carbapenem pressure. The possible selected combinations are currently under study in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of epidemic A. baumannii strains has in fact indicated that genetic relatedness is a poor predictor of the MDR phenotype, supporting the notion that individual strains can independently acquire different mechanisms of resistance (1,12,13,18,34,35,39,49). In this context, localized DNA changes and gene mutations due to mobile genetic elements, resulting in loss, enhancement, or gain of novel functions, as well as remnants of horizontal gene transfer (HGT) from different proteobacterial species, are all represented in the genomes of the A. baumannii clinical strains presently analyzed (1,12,18,35,39,49). Elucidating the contribution of the above-described factors to the shaping of successful nosocomial A. baumannii strains and the acquisition of carbapenem resistance certainly represents a major challenge.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…For example, the ISAba2/ISAba3 element contains the Ϫ35 region of the promoter within the right inverted repeat of ISAba2, while the Ϫ10 region is located within ISAba3. These chimeric promoters vary in the levels of expression of the bla OXA-58-like gene that they drive, suggesting that the use of the carbapenems is selecting for these more complicated genetic structures (89,90).…”
Section: Isaba3mentioning
confidence: 99%